Developing the developmental origins of health and disease (DOHaD) awareness scale to assess an education module for improving dietary behavior among college students - Kadriye Elif İmre; Aslı Akyol (PeerJ, 2024)
Objective This study aimed to develop and validate the Developmental Origins of Health and Disease (DOHaD) awareness scale and examine whether having a DOHaD education module may affect dietary behavior in college students. Background Some studies conducted within the scope of the DOHaD hypothesis show associations between early-life environmental factors, especially maternal health and nutritional status, with the next generation’s health and disease status. Despite the increase in elucidating of the underpinning mechanisms of early life determinants and chronic disease risk, there is limited knowledge on how public perceive and understand DOHaD concepts. Methods The study consisted of three phases: identification of DOHaD awareness scale components, development and validation, interrater reliability of the scale, and a confirmatory study. Two-hundred college students to confirm face validity of the scale, one-hundred for reproducibility and one-hundred for the confirmatory study. Confirmatory study included a pre-intervention period in which baseline parameters (such as anthropometric measurements, HEI-2015 (Healthy Eating Index-2015), physical activity levels, and DOHaD awareness scale scores) were measured at two different time points, and an educational module on DOHaD concepts was provided to the participants. The study was reported in accordance with the Guidelines for Reporting Reliability and Agreement Studies (GRRAS). Results Content validity ratio, exploratory factor analysis, and Cronbach’s alpha values indicated that a reliable and valid instrument to assess the awareness of DOHaD concepts in college students was developed. Despite the lack of a control group, DOHaD concept education was associated with improved anthropometric measurements, healthier eating parameters, increased physical activity levels, and a better understanding of DOHaD concepts. Conclusions Translating DOHaD concepts into healthier behaviors can support improvements in lifestyle, and the use of the DOHaD awareness scale may serve as a valuable tool to encourage healthy behaviors among college students.
Keywords: Male; Adult; Health Knowledge, Attitudes, Practice; Universities; Adolescent; QH301-705.5; Young Adult; Pregnancy; Surveys and Questionnaires; Humans; Biology (General); Students; Health Education; Nutrition; R; Reproducibility of Results; Developmental origins of health and disease; Feeding Behavior; Awareness; Knowledge transition; Medicine; Female; Diet quality